Coping with identity threat and health literacy on the quality of life and mental health in students: Structural equation modeling - Mina Ataei; Sara Esmaelzadeh Saeieh; Mansooreh Yazdkhasti; Alireza Jashni Motlagh (Wiley, 2023)
Abstract Aim Adolescents face many challenges when entering university. The aim of this study was determined predictor role of coping with identity threat and health literacy on the quality of life and mental health of students. Methods This is a descriptive‐analytical study of the structural equation study. Random sampling was performed on 300 students of Alborz University of medical science who were eligible to enter the study. The link of the questionnaires was provided to the students through social networks. The questionnaires were used to study identity threat, mental health, health literacy, and quality of life. Results The results of structural equations showed that health literacy has a negative and significant effect (β = −0.22) and identity threat strategy has a negative and significant effect on students' mental health disorder (β = −0.53). Mental health disorders have a negative and significant effect on the quality of life in students (β = −0.49), and health literacy has a positive and significant effect on the quality of life (β = 0.35). Based on Sobel criterion, mental health disorder was a partial mediator for the indirect effect of coping threat strategy on quality of life. Conclusions Considering the effect of mental health and health literacy on the quality of life and the effectiveness of coping strategies, it is recommended to evaluate the mental health and health literacy of students in universities and provide educational programs for identity coping in the early years after entering the university.